Penerapan “New Media” Website Dalam Pemerintah Daerah Kabupaten Mukomuko - Sazili Sazili; Nesthy Kheren Nadia (Journal on Education, 2024)
The use of new media is now starting to spread to government. The government is currently also intensifying its public information disclosure program in accordance with Law no. 14 of 2008 concerning Openness of Public Information. The research approach model used is qualitative content analysis. Through the government website, the community can benefit from information regarding making KTPs, village funds, government agendas, the latest news in the area where they live, public services, procurement information, government vision and mission, participating in supervising and overseeing government wheels, reporting on government performance, and many more. lots of other information that can be seen. With the many advantages of this new media, the government will also be greatly helped in carrying out its functions, especially in providing information and public services to the community. The public will also be greatly helped by the convenience obtained from the use of new media in the government sector.